Efficacy of Home-Based Electrotherapy for Chemotherapy-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis - Rizqiana Arum Sari; Habib Laksmana Prima; Prasetyo Tri Kuncoro; Raehan Satya Deanasa (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Chemotherapy-induced peripheral neuropathy (CIPN) remains a major survivorship challenge with limited therapeutic options. Neuromodulatory approaches such as transcutaneous electrical nerve stimulation (TENS) have emerged as non-pharmacologic alternatives, but the efficacy of home-based and wearable electrotherapy remains unclear. To evaluate the clinical effectiveness of home-based electrotherapy for improving neuropathic symptoms in patients with established CIPN. A systematic search of PubMed, Cochrane Library, and ScienceDirect (through November 2025) identified randomized controlled and comparative cohort trials evaluating home-based electrotherapy for CIPN. The primary outcomes were changes in neuropathic symptoms (EORTC-CIPN20) and safety. Data were pooled using a random-effects model, with heterogeneity assessed using the I2 statistic. Four studies (n = 236) met the eligibility criteria. Home-based stimulation demonstrated high adherence (>80%) and a favorable safety profile with no serious adverse events. In the exploratory quantitative synthesis (n=3), the pooled standardized mean difference favored the intervention (SMD = −2.19; 95% CI −5.48 to 1.11), although this did not reach statistical significance (p=0.19). Substantial heterogeneity was observed (I2 =98%), likely attributable to variations in device parameters (conventional electrotherapy vs. high-tone) and study populations. Home-based electrotherapy is a feasible and safe adjunct intervention for CIPN with high patient acceptability. While the pooled analysis suggests a trend toward symptom reduction that may be clinically relevant, the high heterogeneity and lack of statistical significance preclude definitive conclusions regarding efficacy. Large-scale, standardized multicenter RCTs are required to confirm these preliminary findings and establish optimal stimulation protocols.